A cross-sectional study on knowledge of the lactating mothers aged 15- 19 towards exclusive breastfeeding in the postnatal clinic at Wakiso Health Centre IV. - Arotin, Babra; Nansereko, Hasifa; Nansereko, Hasifa; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David; Naggulu Posperia, Immaculate (Student’s Journal of Health Research Africa, 2025)
Background. Exclusive breastfeeding is when the infant receives only breast milk and no other foods or fluids, not even water, except oral rehydration solution or syrups containing vitamins, minerals, or medicines, when necessary. This study assessed the knowledge of the lactating mothers aged 15- 19 towards exclusive breastfeeding in the postnatal clinic at Wakiso Health Centre IV. Methodology. A quantitative descriptive cross-sectional study design was used to select 36 mothers using a simple random sampling method, collecting data using a structured questionnaire. Data was analyzed using SPSS computer programs for presentation of tables and figures. Responses for open-ended questions were summarized and given themes before tallying them for analysis. Results. 25(69.4%) of the participants were aged 19 years while the least 1(2.8%), 20(55.6%) of the participants had secondary level of education, 97.2% of the participants had ever heard of EBF, 33.3% did not know the ideal period for EBF, 50% believed EBF is not sufficient for a baby up to 6 months, 25(69.4%) of the respondents mentioned nutritional benefit as the benefit of EBF and 29(91%) of the respondents reported health professional as their source of information about EBF Conclusion. Adolescent mothers at ERRH generally have good knowledge about exclusive breastfeeding (EBF), primarily sourced from healthcare professionals. Recommendations. Expanding education on EBF, especially in antenatal and postnatal care, to address misconceptions and reinforce the six-month duration as essential for infant health.